National Health Interview Survey, 2013 ([Verlag nicht ermittelbar], 2015)
The purpose of the National Health Interview Survey (NHIS) is to obtain information about the amount and distribution of illness, its effects in terms of disability and chronic impairments, and the kinds of health services people receive. The redesigned NHIS questionnaire introduced in 1997 (see NATIONAL HEALTH INTERVIEW SURVEY, 1997 [ICPSR 2954]) consists of a Core that remains largely unchanged from year to year, plus an assortment of Supplements sponsored by other agencies than NCHS, with the assortment varying from year to year. The 2013 NHIS Core components contain Household, Family, Person, Sample Adult, and Sample Child files. Each record in Part 1, Household Level, contains data on type of living quarters, number of families in the household responding and not responding, and the month and year of the interview for each sampling unit. Part 2, Family Level, is made up of reconstructed variables from the person-level data of the basic module and includes information on sex, age, race, marital status, Hispanic origin, education, veteran status, family income, family size, major activities, health status, activity limits, and employment status, along with industry and occupation. As part of the basic module, Part 3, Person Level, provides information on all family members with respect to health status, limitation of daily activities, cognitive impairment, and health conditions. Also included are variables related to doctor visits, hospital stays, and health care access and utilization. A randomly-selected adult in each family was interviewed for Part 4, Sample Adult Level, regarding respiratory conditions, renal conditions, AIDS, joint symptoms, health status, limitation of daily activities, and behaviors such as smoking, alcohol consumption, and physical activity. Part 5, Sample Child Level, provides information from an adult in the household on medical conditions of one child in the household, such as respiratory problems, seizures, allergies, and use of special equipment like hearing aids, braces, or wheelchairs. Part 6, Injury/Poison Episode, is an episode-based file that contains information about the external cause and nature of the injury or poisoning episode and what the person was doing at the time of the injury or poisoning episode, in addition to the date and place of occurrence. Part 7, Family Disability Level, seeks to identify the subpopulation that is at a greater risk than the general population of experiencing restrictions in social participation, for example, restrictions in employment, education, or civic life. Part 8, Adult Functioning and Disability Level, contains information about a respondent's functioning in various basic and complex activity domains: vision, hearing, mobility, communication, cognition, upper body, affect, pain, and fatigue. Part 9, Paradata Level, does not contain health related information, but rather data which are related to the interview process, including measures of time, contact-ability, and cooperation.